Poverty Dynamics in Indonesia: The Prevalence and Causes of Chronic Poverty - Sugiharti, Lilik; Purwono, Rudi; Esquivias, Miguel Angel; Jayanti, Ari Dwi (Journal of Population and Social Studies [JPSS], 2022)
This study aims to determine the chronicity of poverty in Indonesia using the equally distributed equivalent (EDE) poverty gap method, tracking Indonesian households in 2007 and 2014. The results indicate that the largest component of poverty among households was chronic (77%). Compared to transient poverty, chronic poverty is more common across individuals. Unlike previous studies, we used data at the district level to measure the poverty line, discovering that the cost of poverty inequality is lower than often reported. This decision is because disaggregated data (poverty line) can show a more realistic poverty threshold. Using a quantile regression approach, we found evidence that age, gender, employment status, and education were significant factors of chronicity. Other significant factors of chronic poverty include large household size, having no access to services (finance, electricity, information, and mobility), and having limited or no assets. Casual employment in the agricultural sector and living in rural areas increase the probability of poverty, although not necessarily chronic. Poverty alleviation programs, therefore, need to target the right causes as exposure to poverty varies across households.